Breast cancer-specific mutations in CK1epsilon inhibit Wnt/beta-catenin and activate the Wnt/Rac1/JNK and NFAT pathways to decrease cell adhesion and promote cell migration - Foldynová-Trantírková, Silvie; Sekyrová, Petra; Tmejová, Katerina; Brumovská, Eva; Bernatík, Ondrej; Blankenfeldt, Wulf; Krejcí, Pavel; Kozubík, Alois; Dolezal, Tomás; Trantírek, Lukás; Bryja, Vítezslav (Breast cancer research, 2010)
INTRODUCTION: Breast cancer is one of the most common types of cancer in women. One of the genes that were found mutated in breast cancer is casein kinase 1 epsilon (CK1epsilon). Because CK1epsilon is a crucial regulator of the Wnt signaling cascades, we determined how these CK1epsilon mutations interfere with the Wnt pathway and affect the behavior of epithelial breast cancer cell lines. METHODS: We performed in silico modeling of various mutations and analyzed the kinase activity of the CK1epsilon mutants both in vitro and in vivo. Furthermore, we used reporter and small GTPase assays to identify how mutation of CK1epsilon affects different branches of the Wnt signaling pathway. Based on these results, we employed cell adhesion and cell migration assays in MCF7 cells to demonstrate a crucial role for CK1epsilon in these processes. RESULTS: In silico modeling and in vivo data showed that autophosphorylation at Thr 44, a site adjacent to the breast cancer point mutations in the N-terminal lobe of human CK1epsilon, is involved in positive regulation of the CK1epsilon activity. Our data further demonstrate that, in mammalian cells, mutated forms of CK1epsilon failed to affect the intracellular localization and phosphorylation of Dvl2; we were able to demonstrate that CK1epsilon mutants were unable to enhance Dvl-induced TCF/LEF-mediated transcription, that CK1epsilon mutants acted as loss-of-function in the Wnt/beta-catenin pathway, and that CK1epsilon mutants activated the noncanonical Wnt/Rac-1 and NFAT pathways, similar to pharmacological inhibitors of CK1. In line with these findings, inhibition of CK1 promoted cell migration as well as decreased cell adhesion and E-cadherin expression in the breast cancer-derived cell line MCF7. CONCLUSIONS: In summary, these data suggest that the mutations of CK1epsilon found in breast cancer can suppress Wnt/beta-catenin as well as promote the Wnt/Rac-1/JNK and Wnt/NFAT pathways, thus contributing to breast cancer development via effects on cell adhesion and migration. In terms of molecular mechanism, our data indicate that the breast cancer point mutations in the N-terminal lobe of CK1epsilon, which are correlated with decreased phosphorylation activities of mutated forms of CK1epsilon both in vitro and in vivo, interfere with positive autophosphorylation at Thr 44.
Keywords: imunoprecipitace; Phosphorylation; kaseinkinasa Iepsilon; Humans; duktální karcinom prsu; messenger RNA; proteiny Wnt; fosforylace; beta-katenin; Female; mutace; Protein Conformation; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; Wnt Proteins; Cell Adhesion; lidé; Reverse Transcriptase Polymerase Chain Reaction; proliferace buněk; Carcinoma, Ductal, Breast; Casein Kinase 1 epsilon; rac1 GTP-Binding Protein; RNA, Messenger; Breast Neoplasms; ženské pohlaví; pohyb buněk; Cell Proliferation; Cell Movement; beta Catenin; nádorové buněčné linie; nádory prsu; NFATC Transcription Factors; rac1 protein vázající GTP; MAP Kinase Kinase 4; buněčná adheze; Cell Line, Tumor; Immunoprecipitation; Mutation; western blotting; MAP kinasa-kinasa 4; transkripční faktory NFATC; konformace proteinů